University social responsibility: A prospective vision from the functions of teaching, research and extension in the Lisandro Alvarado Centroccidental University (Ágora de Heterodoxias, 2018)
This essay has the purpose of analyzing the university social responsibility from a prospective vision from the functions of teaching, research and extension at the Centroccidental University Lisandro Alvarado. It was conducted a review of documents and other referential intellectual productions that condenses the responsible actions carried out by higher education as a result of the execution of its institutional project in the coherence of its ethical values in the pursuit of happiness through ( a) teaching, not only aimed at training professionals, but also at integrating people into society; (b) research, aimed at developing knowledge, both scientific and technical, that will allow a better quality of life for humanity; and (c) extension, to provide a service to the community with solid ethical and humanistic criteria of solidarity from the academic excellence. These functions with high social standards, from which they will cover the needs and emergencies of the dynamics of emerging changes immersed in the training of future professionals.  It was concluded that the strategic rationality of the university functions should be a transversal axis in the academic formation, with a view to developing a systemic prospective, without disciplinary barriers to assume an unstructured attitude given the complex dynamics of the scientific, technological, organizational and labor advances, in search of greater competitiveness in the context that is glimpsed within the XXI century
Keywords: prospective; social responsibility; functions; university